PENGARUH INFRASTRUKTUR TERHADAP PRODUKTIVITAS EKONOMI DI PULAU JAWA PERIODE 2000-2008 - enik widayati (Media Ekonomi, 2010)
Enik WidayatiKaryawan PT. Cikarang InlandportEmail : pinkitubagus@roketmail.comAbstractInfrastructure is a means to realize the success of a region to increase economicproductivity will also increase economic growth. Economic infrastructure (roads,electricity, telephone, and water) have the potential for it. Like the way that can reducethe cost transoprtasi and simplify the transportation of goods, clean water is available toimprove the quality of healthcare. In this study authors would like to know how theinfluence of economic infrastructure such as roads, electricity, telephone and water supplyon economic productivity in Java (DKI Jakarta, West Java, Central Java, Yogyakarta, EastJava and Banten). The analysis was done using panel data is the data infrastructure(roads, electricity, telephone and water) from 6 provinces in Java Island from 2000 until2008. Processing is accomplished using the eViews 6 with Fixed Effects method. Theregression result shows that the economic infrastructure (roads, electricity, telephone,and water) effect on productivity. Road infrastructure to provide the greatest effectcompared with other infrastructure. So the policy implications of the results of this studyis that the government should pay more attention to infrastructure development becauseof infrastructure will greatly contribute in the economic productivity of priority areas,especially the handling of road infrastructure.Keywords: Productivity, infrastructure roads, electricity, telephone, and water supply